Evaluation of Interest of Young Athletes in Social Media and Cultural Heritage - Halaç, Hicran Hanım; Bademci, Fikret (Mehmet Ali YOLCU, 2021)
Although cultural heritages are assets that need to be protected in terms of the values they contain, today they are in danger of extinction. The basis of this situation is that individuals' awareness of cultural heritage is not at a sufficient level. Both individuals and institutions have important roles in increasing the cultural heritage awareness of societies. In this context, it is important to increase the interest of people who are at the forefront of the society, such as athletes, to cultural heritage and to instil awareness of cultural heritage in these people in spreading awareness of the issue to the society. The aim of the study is to investigate the interests of young athletes in cultural heritage and to reveal their approaches to the cultural heritage they encounter on social media. The universe of the study consists of licensed young athletes actively doing sports in Turkey. Due to the large size of the universe, a stratified sampling method was preferred, and a total of 350 athletes samples, 50s each whom were licensed infrastructure athletes from each of 7 different regions that differ economically, socially and culturally, were selected. The simple random sampling method was preferred as the sampling method in determining the cities in the region where the sampling will be carried out. A descriptive model, one of the quantitative research methods, was used in the study. The questionnaire was preferred as the data collection technique in the study. The data obtained from the surveys were transferred to IBM SPSS STATISTICS 22 program and analyzed and interpreted according to frequency and percentage values. As a result of the research, it was concluded that although they are interested in cultural heritage, they do not have enough information and social media can play an active role in increasing this knowledge level.

Kültürel miraslar barındırdıkları değerler bakımından korunması gereken varlıklar olmasına karşın günümüzde yok olma tehlikesiyle karşı karşıyadırlar. Bu durumun temelinde ise bireylerin kültürel miras bilincinin yeterli düzeyde olmaması yatmaktadır. Toplumların kültürel miras bilinçlerinin arttırılmasında gerek bireylere gerekse kurumlara önemli roller düşmektedir. Bu bağlamda sporcular gibi toplumda ön planda bulunan kişilerin kültürel mirasa olan ilgilerinin arttırılması ve bu kişilere kültürel miras bilincinin aşılanması, konu ile ilgili farkındalığının topluma yayılmasında önem arz etmektedir. Çalışmanın amacı, altyapı sporcularının kültürel miras ilgilerini araştırmak ve sosyal medyada karşılaştıkları kültürel miraslara olan yaklaşımlarını ortaya koymaktır. Çalışmanın evrenini Türkiye’de aktif olarak spor yapan lisanslı altyapı sporcuları oluşturmaktadır. Evrenin geniş olması nedeniyle katmanlı örneklem alma yolu tercih edilerek ekonomik, sosyal ve kültürel anlamda farklılık gösteren 7 farklı bölgeden her birinden 50 lisanslı altyapı sporcusu olmak üzere toplamda 350 sporcuyu kapsayan örneklem seçilmiştir. Bölge içinde örneklemin gerçekleştirileceği şehirlerin belirlenmesinde ise yöntem olarak basit rastgele örnekleme yöntemi tercih edilmiştir. Çalışmada nicel araştırma yöntemlerinden betimsel tarama model kullanılmıştır. Araştırmada veri toplama tekniği olarak anket tercih edilmiştir. Anketlerden elde edilen veriler IBM SPSS STATISTICS 22 programına aktarılarak frekans ve yüzde değerlerine göre analiz edilip yorumlanmıştır. Araştırma sonucunda altyapı sporcularının kültürel mirasa ilgi duymalarına karşın yeterli bilgiye sahip olmadıklarına ve bu bilgi düzeylerinin arttırılmasında sosyal medyanın etkin rol alabileceği sonucuna ulaşılmıştır.
Altyapı Sporcularının Sosyal Medya ve Kültürel Miras İlgilerinin Değerlendirilmesi
Keywords: Cultural Studies; Kültürel çalışmalar